2018
DOI: 10.1089/end.2017.0757
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Patient and Surgical Variables Including Residency Training Level on Adverse Events After Ureteroscopy for Ureteral Stones: A Multivariate Analysis

Abstract: URS has increased in prevalence in recent years, but overall complication rates are low. Resident level of experience does not appear to impact adverse event rate. Stone clearance during initial surgery appears to be the most important in avoiding adverse events. Further expansion of the database over time will improve our ability to predict adverse outcomes in this common procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 7 publications
2
7
0
Order By: Relevance
“…However, in the present study, the stone-free rate achieved by the inexperienced surgeons was 92%, which is comparable with other reports. 12,15 The total complication rate, including ureteral injury and ureteral stenosis, was 8% in the present study, which compared well with those of previous studies, [16][17][18] and particularly well with recently published guidelines, which reported the overall complication rate after f-URS as 9-25%. 16 According to these guidelines, most complications are minor and do not require intervention, and ureteral avulsion and stricture are rare (<1%).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…However, in the present study, the stone-free rate achieved by the inexperienced surgeons was 92%, which is comparable with other reports. 12,15 The total complication rate, including ureteral injury and ureteral stenosis, was 8% in the present study, which compared well with those of previous studies, [16][17][18] and particularly well with recently published guidelines, which reported the overall complication rate after f-URS as 9-25%. 16 According to these guidelines, most complications are minor and do not require intervention, and ureteral avulsion and stricture are rare (<1%).…”
Section: Discussionsupporting
confidence: 91%
“…7 However, the risk of poor stone clearance rates with this technique has been shown to be significant, increasing the likelihood of an adverse event. 12 It has been reported that approximately 20% of patients with residual stone dust or fragments ≤4 mm experience emergency visits within 5 years after f-URS. 13,14 Therefore, it is important to extract stone fragments as thoroughly as possible in f-URS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It may seem intuitive for increased surgeon experience correlating with a decreased operative time; however, there is limited evidence to suggest that this decreased complication rates [45,46]. Wolff et al found that specialist urologists had a lower operative time and complication rate; however, neither of these were statistically significant [20].…”
Section: Increased Surgeon Experiencementioning
confidence: 99%